Experimental study on the cyclic bond behavior of corroded rebar based on modified beam test. (15th April 2022) - Zhang, Xue; Zhao, Yuheng; Zhu, Ziping; Sha, Shuang; Lv, Changming
Abstract: The corrosion of rebar results in the degradation of bond between rebar and concrete, thus is unfavorable to the safety of reinforced concrete structures. So far, many studies were undertaken to investigate the bond behavior of corroded rebars under monotonic loading, however, only a few considered the effect of cyclic loading. Moreover, in these researches, the bond behavior of corroded rebars under cyclic loading were generally studied with pull-out specimens, which cannot ensure an actual stress state of the rebar and concrete during loading. Therefore, in this paper, an experimental study is made to further investigate the cyclic bond behavior of corroded rebars based on a modified beam test, in which the stress state of the rebar and concrete is consistent with reality. Based on the test results, the effects of corrosion level and loading history on the bond stress at a given slip are evaluated. A cyclic bond-slip model is proposed, in which the degradation rule of bond stiffness is calibrated by the test results. The model is implemented in a user-defined bond element and validated with the test results. The predictions of the model show great agreement with the test results, meaning that the proposed model is feasible to simulate the bond stress-slip relationship of corroded rebars under cyclic loading. Highlights: The cyclic bond behavior of corroded rebar is investigated with a modified beam test. The effect of corrosion level and loading history on the bond stress are evaluated. A cyclic bond stress-slip model is proposed for corroded rebar accounting for the actual stress state.